An updated systematic review and Meta-analysis of the prevalence of type 2 diabetes in Iran, 1996–2023 - Hazar, Narjes; Jokar, Mohammad; Namavari, Negin; Hosseini, Saeed; Rahmanian, Vahid (Frontiers in Public Health, 2024)
Background: Diabetes mellitus (DM) poses a significant threat to public health, and the anticipated surge of over 100% in the age-standardized prevalence of type 2 diabetes in Iran between 2021 and 2050 underscores the pressing need for focused attention. The rationale for estimating the prevalence of type 2 diabetes in Iran becomes even more compelling when considering the potential cascading effects on the healthcare system, quality of life, and economic burden. The aim of this study was to estimate the prevalence and trends of DM from 1996 to 2023 in the Islamic Republic of Iran.Methods: Up to July 2023, without deadlines, the search for appropriate articles in Persian and English. Iranian sources including SID, Magiran, and Element were included in the databases, along with foreign ones like PubMed/MEDLINE, Web of Science, Science Direct, Embase, Scopus, ProQuest, and Google Scholar. Using the JBI quality checklist, the study's level of quality was evaluated. Version 14 of STATA was used to carry out the statistical analysis. The Dersimonian and Liard random-effects models were used because of heterogeneity. To investigate the causes of heterogeneity, subgroup analysis and univariate meta-regression were utilized.Sensitivity analysis was then carried out to see how each study's findings affected the final findings. The prevalence pattern over time was also followed using cumulative meta-analysis.Results: There were 53 studies in all, with a combined sample size of 1,244,896 people. Men were predicted to have a type 2 diabetes prevalence of 10.80% (95% CI: 9.1-12.4), while women were assessed to have a prevalence of 13.4% (95% CI: 11.6-15.3). Additionally, the prevalence of diabetes was much higher in the 55-64 age group, coming in at 21.7% (95% CI: 17.5-25.0). The anticipated prevalence of diabetes was 7.